(untitled) (TSUL LEGAL REPORT, 2026)
Illicit drug trafficking has acquired a global scale in recent decades, significantly impacting the socio-psychological atmosphere in society and negatively affecting the economy, politics, and law and order. The article is devoted to the search for political instruments to counter the international drug business. It highlights the leading role of the UN, interregional organizations, and international cooperation programs in the fight against drug trafficking. The article also examines the problem of the spread of drug addiction among some young people and the efforts to combat it, addressing the country’s stance on this pressing issue. The experience of foreign countries in this area, along with the prevention and intervention measures aimed at reducing drug addiction in the population, are also discussed. It is concluded that addressing the drug problem is a common and shared responsibility of states, which requires effective and enhanced international cooperation, as well as an integrated, interdisciplinary, mutually reinforcing and balanced approach through supply and demand reduction strategies.